Fear of Heterosexism Among Sexuality and Gender Diverse Staff and Students. Issue 3 (February 2022) - Brady, Brooke; Asquith, Nicole L.; Ferfolja, Tania; Hanckel, Benjamin
Fear of heterosexism—as distinct from actual experiences of heterosexism—plays a significant role in staff and students lives on campus. Ambient workplace heterosexism provides a context for staff and students about what to expect from their peers and colleagues, and shapes the daily activities of those who perceive heterosexism as a regulating force. In this article, we consider the psychometrics of the Fear of Heterosexism Scale ( FoHS ), which was integrated into a campus climate survey of Western Sydney University staff and students ( N  = 3, 106; n  = 412). This scale was considered in relation to a range of associated factors, including perceived safety on campus, bystander efficacy, responsibility to intervene, and awareness of lesbian, gay, bisexual, transgender, intersex, queer/questioning, asexual, and many other terms such as nonbinary and pansexual (LGBTIQA+) issues. In turn, the results of the FoHS are considered across a range of demographic factors such as gender, sexuality, role, dis/ability, and membership of campus-based support organizations. Supporting the findings from the initial operationalization of the FoHS by Fox and Asquith in 2018, this research identifies the consequences of fear of heterosexism on daily activities and engagement with study/work. Understanding the factors associated with fear of heterosexism is critical in creating more inclusive and respectful university environments.